2000
DOI: 10.1164/ajrccm.161.3.9904116
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Effect of Gentamicin on Nasal Potential Difference Measurements in Cystic Fibrosis Patients Carrying Stop Mutations

Abstract: Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene containing a premature termination signal are expected to produce little or no CFTR chloride channels. It has been shown in vitro, that aminoglycoside antibiotics can increase the frequency of erroneous insertion of nonsense codons hence permitting the translation of CFTR alleles carrying missense mutations to continue reading to the end of the gene. This led to the appearance of functional CFTR channels at the apical plasma membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
1
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(118 citation statements)
references
References 33 publications
2
112
1
3
Order By: Relevance
“…In our study, we focused on nonsense or frameshift mutations leading to PTC resulting in an almost complete absence of particular key proteins involved in lysosomal function and cell homeostasis maintenance. Preclinical studies with gentamicin or PTC124 had succeeded by enhancing stop codon readthrough and were able to be used as therapeutic agents for genetic diseases [9][10][11][12][13][14][15][16][17][18][36][37][38][39][40][41][42]. PTC124 has been successfully extended into clinical trials [18,43], although preliminary results are not clear for Duchenne muscular dystrophy [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we focused on nonsense or frameshift mutations leading to PTC resulting in an almost complete absence of particular key proteins involved in lysosomal function and cell homeostasis maintenance. Preclinical studies with gentamicin or PTC124 had succeeded by enhancing stop codon readthrough and were able to be used as therapeutic agents for genetic diseases [9][10][11][12][13][14][15][16][17][18][36][37][38][39][40][41][42]. PTC124 has been successfully extended into clinical trials [18,43], although preliminary results are not clear for Duchenne muscular dystrophy [44].…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine is preferably inserted at nonsense UAG or UAA codons, whereas UGA miscode to tryptophan [36][37][38]. Taking into account these rules, the predicted amino acid changes were analyzed, using an in silico approach, for each patient (Polyphen-2 and SIFT analyses).…”
Section: In Silico Analysis Of the Predicted Substitutions Induced Bymentioning
confidence: 99%
“…These results thus strongly suggest that only a subset of DMD and CMD patients carrying stop mutations would potentially benefit of a gentamicin treatment aiming at suppressing premature termination codons. They may also explain the failure or relative difficulty to obtain significant improvement of symptoms in clinical trials already reported, [34][35][36] since the patients included in these trials were not chosen on the criteria of the response of their mutation. Similarly, Gentamicin and muscular dystrophies L Bidou et al our efforts to correct the albino phenotype associated with the platinum (Typ cÀp ) coat color mutation by local or systemic treatment with gentamicin at several stages during embryogenesis, in pups and in adults failed (data not shown).…”
Section: Different Rules Govern Basal and Induced Readthroughmentioning
confidence: 99%
“…However, other studies have reported neither the presence nor absence of gentamicin in the nucleus (Hashino et al 1997;Sundin et al 1997;Girton et al 2002). Nonetheless, a subset of cystic fibrosis patients can be partially rehabilitated through gentamicin therapy, which causes bypassing of the premature stop codon in the cystic fibrosis (CF) mutation, allowing functional transcription of the CF transmembrane protein (Howard et al 1996;Bedwell et al 1997;Wilschanski et al 2000;Clancy et al 2001;Du et al 2002;Zsembery et al 2002). This suggests that gentamicin can enter the nucleus.…”
Section: Consequences Of Gentamicin Accumulationmentioning
confidence: 99%